Isolation and characterization of rhizospheric Streptomyces spp. for the biocontrol of Fusarium wilt (bayoud) disease of date palm (Phoenix dactylifera L.) - Mouloud, Ghadbane; Samir, Medjekal; Laid, Benderradji; Daoud, Harzallah (Journal of Scientific Agriculture, 2017)
Fusarium wilt of date palm (Phoenix dactylifera L.) caused by Fusarium oxysporum f.sp. Albedinis is one of the most destructive diseases in North Africa spicily in Algeria and Morocco. The objectives of this work were the isolation, identiﬁcation and biocontrol efﬁcacies testing of rhizospheric actinobacteria of medicinal plant Astragalus gombo against fusarium wilt disease in date palm. Five rhizospheric Streptomyces spp. Isolates bi02, bi21, bi24, bi26 and bi28 showed the largest zone of inhibition demonstrating a potent effect against F. oxysporum f.sp. Albedinis and a broad spectrum of antimicrobial activities against the test microorganisms. All these selected isolates produced indol acetic acid (IAA) at different levels, exhibited higher activity of phosphate solubilisation and siderophore production as well as chitinase and protease activities. The inoculation of infected date palm with the five Streptomyces spp. Increased all parameters of growth measured in controlled conditions. The study revealed that the five Streptomyces spp. could be a potential biocontrol agent for controlling palm and also promoting growth of plants.